Potential relationship between self-efficacy beliefs and proficiency in grammar among tertiary EFL learners - Kholili, Achmad (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
A multitude of studies on self-efficacy beliefs have been undertaken to date, especially in language learning. However, little evidence is given on looking into the relationship between self-efficacy and English grammar. To this end, the present study goes about identifying to what extent the correlation between learners’ self-efficacy and their achievements in the grammar test is. Drawing on the correlational design, an English grammar test was administered to the learners to know the learners’ acquaintance with the English grammar. Meanwhile, a self-efficacy questionnaire was performed by the researcher to the learners to figure out to what extent their efficaciousness is. A Pearson-product moment correlation was performed to analyze the relationship between such variables. The result demonstrates that there is a high positive significant correlation between learners’ self-efficacy and their attainments in the grammar test, displayed by r Correlation = +1. This finding brings a recent insight in the field of language learning.